MOLECULAR CHARACTERIZATION OF CARBAPENEM RESISTANT KLEBSIELLA PNEUMONIAE AT A TERTIARY CARE LABORATORY IN KERALA, INDIA - C. Senan, Swapna; Paul Jacob, Jithu; Bhai, Ramani (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: Isolates of Klebsiella pneumoniae resistant to Carbapenem appears to be most commonly transmitted by hospitalized patients. This may cause infections which lead to mortality. Therefore, studies on molecular level will help to gain more information and be able to know their cross-transmission and resistance mechanisms among these isolates showing resistance. Purpose: Investigate the molecular characterization of carbapenem-resistant Klebsiella pneumoniae isolates from various clinical samples. Klebsiella pneumoniae are aerobic and Gram-negative bacilli found in the gastrointestinal tract of humans and other animals and also as saprophytes in soil. Method: In this study, 401 bacteria of Klebsiella isolates were taken from various clinical samples according to standard protocol. Carbapenem-resistant genes of Klebsiella pneumoniae (CRK) isolates were detected using multiplex polymerase chain reaction (PCR). Result: The twelve isolates resistant to carbapenem were confirmed phenotypically and were confirmed using a multiplex Polymerase Chain Reaction. Conclusion: The present study concluded that identification of Carbapenem-resistant genes of Klebsiella pneumoniae (KPC) could help find out the routes of dissemination of the species and may control its spread within the hospital premises.